Settlement of Islamic Sharia Violations in the Perspective of Teungku Dayah and Local Wisdom Values on the West Coast of Aceh - Syamsuar, Syamsuar; Al-Fairusy, Muhajir; Junaidi, Junaidi; Mulia, Muji (Jurnal Ilmiah Peuradeun, 2023)
The implementation of Islamic Sharia in Aceh has experienced dynamics since it was first implemented in early 2000—the presence of pro and contra attitudes from the community towards the interpretation and existence of Islamic Sharia. As a result, a model for resolving sharia violations based on local values ​​often emerges. This study departs from the central question of why the people of Aceh often choose local deals in determining several breaches of Islamic law in society. This study seeks to analyze the resolution of violations of Islamic law in the border areas of Aceh with local consensus values. The phrase border Aceh refers to a multi-identity place (ethnicity and religion). This study combines two concepts between local wisdom and Islamic law. The research method uses a qualitative approach with grounded research. The study results show that people who live on the border of Aceh, especially several districts on the West Coast of Aceh, often choose a local (non-Sharia) approach in cases of violations of Islamic Sharia. Settlements with local values ​​are considered more readily accepted by the community. Interestingly, this study found that the role of local wisdom can also reduce the number of violations of Islamic law in the border communities of Aceh.